Pokemon Go and the hospitality industry the effects of the game and related promotions to customer preferences of restaurants - Rebadavia, Juan Miguel G.
Pokemon Go was an augmented reality mobile game created by the company Niantic, ,which became a worldwide trend. Its popularity came to an extent that even businesses such as restaurants in the hospitality industry were incorporating the game into their marketing strategies to help attract customers. What athe researcher looked into in this study was if the mobile application and related promotions had an influence to consumer preferences of which restaurants to visit. The statistical significance between that and the demographic profiles of age, sex and occupational groups was also determined. Related literature stated that designation of restaurants as Pokestops and Pokegyms, lures, spawning of Pokemon, freebies, discounts, Pokemon inspired items, and free Wi-Fi and charging, were some of the marketing strategies used by businesses. It was also said that, through such related promotions, the restaurants were benefiting from the game's popularity, as customers were flocking to these establishments because of it. This was until the trend started decline to be perceived as onky a possible pad. After. The researcher conducted a survey of 89 respondents, the results showed that pokestos and Pokegyms in or near restaurants was most perceived as an effective marketing strategy for restaurants to attract customers, one they were also most aware of. However, for the effect of Pokemon Go and related promotions to customer behavior, most of the respondents thought that it did not generally influence their choices of which restaurant to visit. Between that and all demographic variables, there was no significant difference. Therefore, it was concluded that Pokemon Go was only a perceived fad that, despite its potential bebefits to businesses in terms of sales, had no impact to customer preferences of food establishments.